Perencanaan Fasilitas Pelayanan Publik Berbasis Green City di Kawasan Industri Pangkep (KIPA) Kabupaten Pangkep - Saryanti Mustakin; Muhammad Fathien Azmy; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
The development of industries in Pangkep Regency is increasing, especially in large industries such as those in the area around the mine, namely PT. Semen Tonasa and Marble in Bungoro and Minasate'ne Districts. The location of these large industries is near residential areas without any boundaries or green fiber which limits settlements to industrial locations. This study aims to create a green city concept in the Pangkep Industrial Zone (KIPA) in the provision of public service facilities for the next 20 years. The data used in this study are the number of residents, existing conditions, number and radius of achievement of public, social and economic public service facilities. Data were analyzed in the calculation of projections, where the population projection data in 2034 was used as data to find out the number of public service facility needs in 2034, while spatial analysis was used to see the placement of each facility to serve residential settlements based on the radius of achievement of each of these facilities. The results of this study are, planning for public service facilities with the concept of green city in Pangkep Industrial Estate in 2034. Planning for public service facilities with this concept is to bring the facilities needed by residents to the location of settlements to civilize the community walking or using bicycles to reduce air pollution due to motorized vehicles and plan green spaces of up to 50% of the total area, especially the green fiber of the industrial area, to prevent the direct impact of the industry on residents' settlements.